American wolf [compact disc, unabridged] : a true story of survival and obsession in the West - Blakeslee, Nate, 1970- (Random House Audio, 2017)
The enthralling story of the rise and reign of O-Six, the celebrated Yellowstone wolf, and the people who loved or feared her.